2021
DOI: 10.1186/s12866-021-02243-w
|View full text |Cite
|
Sign up to set email alerts
|

Chitin-rich heteroglycan from Sporothrix schenckii sensu stricto potentiates fungal clearance in a mouse model of sporotrichosis and promotes macrophages phagocytosis

Abstract: Background Fungal cell wall polysaccharides maintain the integrity of fungi and interact with host immune cells. The immunomodulation of fungal polysaccharides has been demonstrated in previous studies. However, the effect of chitin-rich heteroglycan extracted from Sporothrix schenckiisensu stricto on the immune response has not been investigated. Results In this study, chitin-rich heteroglycan was extracted from S. schenckiisensu stricto, and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In general terms, in an experimental model of systemic sporotrichosis, mice can be inoculated intraperitoneally or intravenously either in the tail vein or in the retro-orbital plexus (Tachibana et al, 1998;Fernandes et al, 1999). For a disseminated Tachibana et al, 1998;Fernandes et al, 1999;Nascimento and Almeida, 2005;Kong et al, 2006;Brito et al, 2007;Arrillaga-Moncrieff et al, 2009;Ruiz-Baca et al, 2009;Teixeira et al, 2009Teixeira et al, , 2010Almeida-Paes et al, 2012Castro et al, 2013;Clavijo-Giraldo et al, 2016;Martinez-Alvarez et al, 2019;García-Carnero et al, 2021;Song et al, 2021 Host innate response Shiraishi et al, 1992;Sassá et al, 2009;Guzman-Beltran et al, 2012;Guzman Beltrán et al, 2021;Romo-Lozano et al, 2012Sandig and Bulfone-Paus, 2012;Negrini Tde et al, 2013;de Almeida et al, 2017de Almeida et al, , 2018Martinez-Alvarez et al, 2017Lozoya-Perez et al, 2018Lozoya-Pérez et al, 2020;Lozoya-Perez et al, 2021;Rossato et al, 2019;Huang et al, 2021;Tamez-Castrellón et al, 202...…”
Section: Systemic and Peritoneal Models Of Sporotrichosis In Micementioning
confidence: 99%
See 1 more Smart Citation
“…In general terms, in an experimental model of systemic sporotrichosis, mice can be inoculated intraperitoneally or intravenously either in the tail vein or in the retro-orbital plexus (Tachibana et al, 1998;Fernandes et al, 1999). For a disseminated Tachibana et al, 1998;Fernandes et al, 1999;Nascimento and Almeida, 2005;Kong et al, 2006;Brito et al, 2007;Arrillaga-Moncrieff et al, 2009;Ruiz-Baca et al, 2009;Teixeira et al, 2009Teixeira et al, , 2010Almeida-Paes et al, 2012Castro et al, 2013;Clavijo-Giraldo et al, 2016;Martinez-Alvarez et al, 2019;García-Carnero et al, 2021;Song et al, 2021 Host innate response Shiraishi et al, 1992;Sassá et al, 2009;Guzman-Beltran et al, 2012;Guzman Beltrán et al, 2021;Romo-Lozano et al, 2012Sandig and Bulfone-Paus, 2012;Negrini Tde et al, 2013;de Almeida et al, 2017de Almeida et al, , 2018Martinez-Alvarez et al, 2017Lozoya-Perez et al, 2018Lozoya-Pérez et al, 2020;Lozoya-Perez et al, 2021;Rossato et al, 2019;Huang et al, 2021;Tamez-Castrellón et al, 202...…”
Section: Systemic and Peritoneal Models Of Sporotrichosis In Micementioning
confidence: 99%
“…This is an ongoing debate in this area that remains to be solved. In addition, instead of cells, soluble antigenic preparations from S. schenckii can be isolated and used to inoculate mice (Carlos et al, 1992 ; Huang et al, 2021 ). External factors such as culture media, cell longevity, and maintenance conditions should also be considered during the analysis of the host-fungus interaction since they have been reported to influence cell wall composition, fungal morphogenesis, and virulence (Lopes-Bezerra et al, 2018b ; Lozoya-Pérez et al, 2020 ).…”
Section: Mammalian Models To Study Sporotrichosismentioning
confidence: 99%
“…S. globosa showed a higher amount of cell wall glucosamine, i.e., chitin, when compared to the other two species, but this was mostly in the inner cell wall; the only exception was in yeast-like cells, where this was more exposed. Higher exposure to chitin in the fungal cell wall may be related to a lower virulence, since it has been reported that chitin-rich heteroglycan extracted from S. schenckii protects the host against infection caused by this species by increasing fungal clearance, phagocytosis, and the production of pro-and anti-inflammatory cytokines to modulate the immune response [71]. Even though we did not address melanin production in the cell preparation used in this study, it is worth noting S. globosa melanin inhibits the expression of antigen presentation-associated molecules and fungal phagocytosis [72] and protects against oxygen and nitrogen radicals, decreasing TNFα and IL-6 production [73], which is in concordance with the cytokine profile reported here for the three S. globosa morphologies.…”
Section: Discussionmentioning
confidence: 99%
“…Different mushrooms have been identified as sources of biologically active polysaccharides. The majority of them seem to be homoglycans, with some are heteroglycans; however, they may also be identified to be conjugate with proteins, creating polysaccharide–protein or peptidoglycans complexes (proteoglycans) [59]. β‐Glucans are among the most extensively reported polysaccharides isolated from Basidiomycetes .…”
Section: Chemistry and Synthesis Of Fungal Polysaccharidesmentioning
confidence: 99%